Central systolic pressure and a nonessential amino acid metabolomics profile - Catharina M. C. Mels; Christian Delles; Roan Louw; Aletta E. Schutte (2019)
Objectives: Early-life exposures to cardiovascular risk factors may manifest as early vascular ageing, a phenomenon to which black populations are more prone. The metabolome provides insight into the current state and regulation of physiological processes and was used to investigate the early molecular determinants of arterial stiffness. Methods: Black (N = 80) and white (N = 80) men and women (aged 20–30 years, clinic blood pressure <140 and 90 mmHg) across the arterial stiffness spectrum were included. Carotid–femoral pulse wave velocity, central SBP (cSBP) and central pulse pressure (cPP) were measured. NMR spectroscopy, liquid chromatography tandem mass spectrometry and gas chromatography–time of flight-mass spectrometry methods produced metabolomic data. Results: Differences (d ≥ 0.3) in 34 metabolites between black and white groups were found (adjusted for multiple comparisons). Only cSBP were higher in the black group (P = 0.003). Lower dietary protein intake (P < 0.001), but higher urinary nonessential amino acid levels were found in the black group (q ≤ 0.05). In multivariable-adjusted regression models cSBP and cPP inversely correlated with various nonessential amino acids, but only in black adults. These include associations of cSBP with 4-hydroxyproline (β = −0.24; P = 0.042), alanine: (β = −0.29; P = 0.015), glutamine (β = −0.25; P = 0.028), glycine (β = −0.26; P = 0.027), histidine (β = −0.30; P = 0.009), serine (β = −0.29; P = 0.012), and associations of cPP with alanine (β = −0.31; P = 0.005) and serine (β = −0.26; P = 0.019). Conclusion: These amino acids play pivotal roles in collagen metabolism, glucose metabolism and oxidative stress and this ethnic-specific finding suggests that biosynthesis of nonessential amino acids may be upregulated to protect the vasculature against the onset of early vascular deterioration.